Return-to-work rates and predictors of absence duration after COVID-19 over the course of the pandemic - Aben, Bart; Kok, Robin N.; de Wind, Astrid (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVES ': 'The aim of this study was to evaluate employee return-to-work (RTW) rates and examine predictors of absence duration after COVID-19. RTW rates were referenced against RTW rates after absence due to flu-like symptoms and assessed over the course of the pandemic. ' ' METHODS ': 'Routinely collected data from a nationally operating Dutch occupational health service was used. The data were retrieved from employees who reported sick due to COVID-19 (N=30 396) or flu-like symptoms (N=15 862). Data consisted of responses to a triage survey combined with longitudinal register-based information on sickness absence. RTW rates after COVID-19 were evaluated through Kaplan-Meier estimates and compared to RTW rates for flu-like symptoms, and between three periods with different dominant virus variants. Predictors for absence duration were examined through Cox proportional hazards models. ' ' RESULTS ': 'RTW after COVID-19 was found to be notably later than after flu-like symptoms (median RTW=10 versus 6 days, respectively). On average, 5.5% of employees who contracted COVID-19 were absent for over 12 weeks. Time-to-RTW shortened as different virus variants became dominant over time. The main predictors contributing to later RTW were older age, female sex, belonging to a risk group, and the symptoms shortness of breath and fatigue. ' ' CONCLUSIONS ': 'Estimates of the RTW rate after COVID-19 and identification of predictors may aid healthcare professionals in gaining insight into variations in the disease course and rehabilitation process. The present findings can help employers and policy-makers grasp the impact of COVID-19 on the workplace.
Keywords: absence; COVID-19; Cox proportional hazards model; long COVID; occupational health; pandemic; predictor; return to work; return-to-work; RTW; SARS-Cov-2; sick leave; sickness absence; survival analysis